Energy saving of benzene separation process for environmentally friendly gasoline using an extended DWC (divided wall column). (1st April 2016) - Kim, Young Han
Abstract: Benzene is a known carcinogen, and is desired to be removed from the gasoline additive for environmental reason. A benzene removal process from the additive, reformate of catalytic reformers, is proposed utilizing an extended DWC (divided wall column). The DWC reduces the processing load of the whole process especially in extractor, which employs high boiling point solvent requiring large amount of energy and costly utility. In this study the design of the proposed process is addressed along with the evaluation of energy saving, economics and thermodynamic efficiency. The evaluation results indicate the heating duty reduction of 56.8% from the proposed process over the conventional process and 64.6% reduction of cooling duty. The economics reveals the 26% reduction of investment and 56% reduction of utility cost from the proposed process. However, no significant improvement of thermodynamic efficiency is yielded. Highlights: Energy saving benzene separation process is proposed. Extraction load is reduced by feed separation. Heat duty saving of 57% is yielded. Investment and utility cost savings are 26% and 56%. Commercially proven DWC is utilized.